Curating born-digital archives at the Bodleian Library - Thomas, S (2010)
Individuals and organisations operate in an increasingly digital landscape, and one that presents a range of challenges and opportunities to archive creators, repositories and scholars. This presentation will address some of the issues that come into play now that manuscripts are 'born-digital'; it will also describe how the future Arch project is enabling the Bodleian to respond to this change, by providing facilities for depositors, curators and readers.